RISK MANAGEMENT OF GENERATING ENERGY COMPANIES - E. Kamchatova (Вестник университета, 2018)
The purpose of the study is to determine factors causing the occurrence of risk situations for power generating companies. This article presents a general risk profile. Subject of research are the risks that arise in economic systems, process management. As a result of systematic studies the risk factors which are grouped on the basis of their occurrence on the basis of peculiarities of functioning of the generating companies was found. The methods to reduce risks for power generating companies in terms of modern realities are suggested.